Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jwmg.21504
|View full text |Cite
|
Sign up to set email alerts
|

Sample size considerations for satellite telemetry and animal distributions

Abstract: Satellite telemetry is a powerful tool used to follow animals through their annual life cycle, informing the understanding of behavior and distribution of many species. Because boreal‐ and arctic‐nesting North American sea duck populations are challenging to survey, satellite telemetry is important for describing breeding distributions and identifying breeding population structure. Accurate knowledge of breeding distributions is needed for effective habitat and harvest management, but satellite telemetry is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition, generating a representative network requires distributing transmitters throughout the population(s) of interest. This study benefited from a coordinated effort to deploy transmitters throughout the populations of interest, resulting in comprehensive coverage of scoter species' ranges (Pearce et al 2019) with sample sizes sufficient to characterize seasonal distributions (ie at least 80-130 individuals per species; Roberts et al 2018). However, low-density wintering areas (eg the Gulf of Mexico for black scoters) were unsampled and are underrepresented in the network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, generating a representative network requires distributing transmitters throughout the population(s) of interest. This study benefited from a coordinated effort to deploy transmitters throughout the populations of interest, resulting in comprehensive coverage of scoter species' ranges (Pearce et al 2019) with sample sizes sufficient to characterize seasonal distributions (ie at least 80-130 individuals per species; Roberts et al 2018). However, low-density wintering areas (eg the Gulf of Mexico for black scoters) were unsampled and are underrepresented in the network.…”
Section: Discussionmentioning
confidence: 99%
“…2019) with sample sizes sufficient to characterize seasonal distributions (ie at least 80–130 individuals per species; Roberts et al . 2018). However, low‐density wintering areas (eg the Gulf of Mexico for black scoters) were unsampled and are underrepresented in the network.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling parameters are dictated by the cost, size, and technological limitations of tracking devices, rather than designed to maximize statistical power of the results to detect target patterns of movement [ 1 , 2 ]. Nevertheless, accumulation of tracking data over time has created opportunities to synthesize existing data and assess how the number and distribution of sampled individuals affects detection of variation and population-level inferences [e.g., 3 , 4 ]. Such retrospective studies have generally focused on active transmitters that actively collect, store, and/or upload location data via satellite networks.…”
Section: Introductionmentioning
confidence: 99%
“…The number collared may be too low to get accurate estimates of the UD. Seaman et al (1999) estimated that at least 30 observations (but preferably ≥ 50) are necessary using KDE with least-squares cross validation to estimate the smoothing bandwidth and other studies have suggested much larger samples are necessary (Arthur & Schwartz, 1998;Lindberg & Walker, 2007;Roberts et al, 2018). In practice, this means that achieving an adequate sample size from collared individuals may require combining multiple years of location data or may not be possible.…”
Section: Introductionmentioning
confidence: 99%